2013
DOI: 10.5507/bp.2012.089
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of Fisturalin-3 and 11-Deoxyfisturalin-3 on Jurkat and U937 cell lines

Abstract: Background. Fisturalines are bromotyrosine compounds isolated from marine sponges. Previous studies have shown antineoplasic, antiviral and antibacterial effects in Vitro; however, the possible effects of these compounds in hematologic malignancies have not been assessed. Methods. In the present study, the antiproliferative and pro apoptotic effects of Fistularin-3 (F) and 11-Deoxyfistularin-3 (DF) were assessed using the MTT method and annexin V/propidium iodide by flow cytometry using the cell lines: Jurkat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…No mechanistic study has been conducted so far to investigate the anticancer activity of this molecule. Nevertheless, cytotoxic activity against HeLa cells has been reported for Iso-3 [ 17 ], and a cytostatic effect was reported for Iso-3 structural isomer fistularin-3, against hematological cancer lines [ 18 ], indicating potential benefits in the use of Iso-3 against cancer.…”
Section: Introductionmentioning
confidence: 99%
“…No mechanistic study has been conducted so far to investigate the anticancer activity of this molecule. Nevertheless, cytotoxic activity against HeLa cells has been reported for Iso-3 [ 17 ], and a cytostatic effect was reported for Iso-3 structural isomer fistularin-3, against hematological cancer lines [ 18 ], indicating potential benefits in the use of Iso-3 against cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Bromotyrosine derivatives comprise several biologically active molecules [23,24,27,59]. We previously showed that isofistularin-3 docked into the DNMT1 DNA-binding CXXC domain and inhibits in vitro DNMT1 activity [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we described the compound isofistularin-3 from Aplysina aerophoba to act as a cytostatic drug against a panel of cancer cell lines and sensitizes lymphoma cell lines to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) [22]. Fistularins are a family of sponge-derived brominated tyrosine found in various genera of sponges, comprising molecules with cytotoxic activity against cancer cells [23,24,25,26,27]. Recently, fistularin-3 was also recognized in cultures of the marine bacterium Pseudovibrio denitrificans Ab134 isolated from the sponge Arenosclera brasiliensis [28], which evokes a potential use of microorganisms for sustainable supplies of complex marine molecules in drug development.…”
Section: Introductionmentioning
confidence: 99%
“…An Epics XL cytometer (Beckman Coulter, Indianapolis, IN, USA) was used for the analysis. Untreated cells were the negative controls, and doxorubicin (Dox) (1 µM), and quercetin (QC) (50 µM) were the positive controls [ 64 , 65 , 66 ]. Early apoptosis refers to annexin V expression, late apoptosis, the coexpression of annexin V and PI, and necrosis the sole expression of PI.…”
Section: Methodsmentioning
confidence: 99%